THEORETICAL FUNDAMENTALS OF E-BUSINESS DEVELOPMENT - LYASHEVSKA, Viktoriia; DANILEYKO, Elizaveta; DYACHENKO, Yuliia (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article explores different approaches to the definition of "e-business". It was determined that e-business is a set of basic business processes that are formed using Internet technologies. E-business is one of the types of economic activity, which is implemented using information and communication technologies in the management of business processes, in order to obtain maximum profits. The main task of e-business is the use of modern information technology to replace old business models with new ones in order to improve the quality of the organization. Due to the modernization of old processes, the development of competition is intensified and that is why the management of any organization must respond as soon as possible to the constantly changing market situation and adapt to it accordingly or find a way out. Rapid adaptation and the ability to implement new ideas in their business processes help to improve many performance indicators of the enterprise. E-business is the common name of many of its types, so it is divided into e-commerce, e-education services, e-financial services, e-payment services, e-marketing and consulting, e-business in the field of employment and information. All these species are already formed at the moment and are developing. The article introduces the concept of e-commerce and emphasizes the difference between it and e-business. The main differences between these two concepts are given. The article also explores the means of providing business processes and the principles of forming an e-business infrastructure. Its advantages and disadvantages, strengths and weaknesses are identified using SWOT-analysis. They learned what factors hinder the development of e-business in Ukraine and suggested measures to grow this area.
Keywords: e-commerce; e-business; virtual business; business processes